Extração, purificação e aplicação do ácido fítico de farelo de arroz - Bloot, Ana Paula Marinho (2016)
This study aims was to develop a method for extraction of defatted rice bran (DRB) phytic acid using ultrasonic bath and its subsequent purification by anion exchange resin, and evaluate the inhibitory effects of phytic acid standard (dodecasodium phytate from rice) on the C. perfringens type A spore outgrowth and growth of vegetative cells. A 23 factorial design with five central point was used to the ultrasonic bath extraction, and the independent variables were pH of extraction, ultrasound power, and the extraction time (minutes). The results showed that the amount of phytic acid extracted at a frequency of 80 kHz was higher than that extracted at 37 kHz (p ≤ 0,05). By the factorial design was verified that only the variable pH had a significant effect (p ≤ 0,05) on the extraction. In purification, by the batch adsorption experiments, was found that the Purolite A111 resin showed a satisfactory adsorption capacity compared to the other resins tested, and the batch adsorption data were better fitted by the Langmuir adsorption isotherm (R2 = 0,9650%). The results from preliminary desorption tests showed that only the solution of 1.0 mol L-1 NaCl was able to desorb phytic acid from A111 resin, and therefore, this solution was used in the batch desorption experiments. The batch desorption results were modelled and best fitted by the Langmuir isotherm model (R2 = 0,9920). The adsorption results of fixed bed column were satisfactorily fitted by the Yoon-Nelson empirical model (R2 = 0,9417). The A111 resin showed satisfactory results in adsorption and desorption by batch and fixed bed column experiments in the phytic acid purification. After purification experiments, the inhibitory effects of phytic acid pattern on the spores outgrowth and growth of vegetative cells of C. perfringens was evaluated. It was observed that the BHI medium supplemented with standard phytic acid has inhibited satisfactory the C. perfringens spores outgrowth at least for 9,5 hours of incubation. In the vegetative growth of C. perfringens in BHI medium supplemented with 1,0% standard phytic acid, there was growth inhibition, with an effective inhibition for at least 8 hours. This inhibitory effect was similar to the 10% sodium sorbate (p ≥ 0,05). Finally, the results showed the development of a new and efficient technique for phytic acid extraction and purification, providing a considerable reduction in the extraction time and a high yield of phytic acid extracted. This, after purified had a high purity (79,78%). Moreover, the standard phytic acid was effective as an inhibitor of spores and vegetative cells of C. perfringens